2004
DOI: 10.2466/pms.99.1.341-353
|View full text |Cite
|
Sign up to set email alerts
|

Mood Changes after Maximal Exercise Testing in Subjects with Symptoms of Exercise Dependence

Abstract: Considering exercise has positive and negative reinforcing properties, the mood states of sedentary, nonexercise-dependent and exercise-dependent volunteers were compared after maximal exercise testing. Mood status was evaluated by the Beck Depression Inventory, Trait-State Anxiety Inventory, and Profile of Mood States (POMS). No differences were detected before the test or after it, indicating little possibility of positive reinforcement. However, a significant reduction in the POMS Tension-Anxiety scores was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
2
0
4
Order By: Relevance
“…Research shows that exercise addiction, like a compulsion, is maintained by its mood-altering effects. However, these effects extend beyond anxiety reduction to include lessening other negative affects including anger [21], depression, and boredom [11]. Unlike compulsive behavior, addictions are also maintained by enhancement of positive affect.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that exercise addiction, like a compulsion, is maintained by its mood-altering effects. However, these effects extend beyond anxiety reduction to include lessening other negative affects including anger [21], depression, and boredom [11]. Unlike compulsive behavior, addictions are also maintained by enhancement of positive affect.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, em alguns indivíduos, essa prática pode levar a um sentimento de obsessão-compulsão, conhecido como DE, e que resulta em um comportamento incontrolável em praticar exercício físico de forma excessiva, podendo influenciar algumas esferas da vida (15)(16)(17)(18)(19)(20)(21)(22) . O proposto em nosso estudo foi verificar se a variável financeira pode causar interferência no que se diz respeito ao surgimento dessa dependência ou nas formas de sua manifestação.…”
Section: Discussionunclassified
“…Além disso, encontramos também que os atletas amadores dependentes de exercício praticantes de modalidades individuais apresentam escores maiores na dimensão raiva-hostilidade pelo Questionário POMS. Na mesma comparação no grupo profissional individual, observamos maiores valores de depressão em atletas dependentes de exercício, o que confirma a hipótese de que a dependência de exercício físico pode alterar negativamente o humor dos atletas (21,22,25) . Em outra analise, dentro dos grupos, observamos que atletas de modalidades esportivas coletivas apresentam melhores escores de humor e qualidade de vida quando comparados com atletas praticantes de modalidades individuais, tanto para atletas dependentes de exercício físico como para não dependentes, o que também sugere que fatores ambientais e sociais estão intimamente ligados ao humor e à qualidade de vida (17,20,23,25) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The main hypotheses proposed by studies about exercise addiction are those related to both physiological and psychological factors associated with the practice of physical exercises (for a review see Hamer;Karageorghis (2007). Rosa et al (2004) used the same exercise dependence scale and measured the alteration in mood state after an acute exercise test of three distinct groups: sedentary subjects, exercisers with low levels of exercise dependence and exercisers with high levels of exercise dependence. In his study, it was found that only exercisers with high levels of addiction were the most prone to changes mood states induced by an acute exercise test, indicating that for these subjects, exercise produced a negative reinforcement that contributed to the development of exercise dependence.…”
Section: Discussionmentioning
confidence: 99%